Methods and techniques for evaluating non-marketable ecosystem services - Gabriela Elena Baciu; Ioana Toma; Cristina Gârlea (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Ecosystems provide a range of goods and services vital to the well-being of humans and other living things, as well as to the development of society. Along with natural resources, tangible and tradable in the market, they provide a series of intangible, non-marketable services that translate into health, cultural, social and scientific benefits. Human activities, especially after industrialization, have created unprecedented pressures on natural ecosystems and led to their constant degradation, resource depletion, global warming and loss of biodiversity. This is also because non-marketable services are underestimated by the majority of the population, being perceived as inexhaustible and free. The health of ecosystems has a direct impact on the quality of life of people and other living things, a fact that has led to the development of a series of methods and techniques for evaluating all services, including non-marketable ones, so that their value can be taken into account at all relevant levels of the decision-making process. In this paper, a state-of-the-art of methods and techniques for evaluating non-marketable services provided by ecosystems is presented, the results of studies to calculate the Total Economic Value of ecosystem services are presented, as well as their importance in the process of public policy development.
Keywords: Q51; 330; ecosystem services; global warming; biodiversity; evaluation methods; public policies